Prolonged SARS‐CoV‐2 infection during obinutuzumab and bendamustine treatment for follicular lymphoma: A case report - Ryosuke Kambe; Masamichi Sato; Daisuke Uehara; Yutaka Iizuka; Satoru Kakizaki (Clinical Case Reports, 2023)
Key Clinical Message SARS‐CoV‐2 infection has been associated with a prolonged course and a poor prognosis in patients who receive anti‐CD20 antibodies. However, there are no established treatments for such patients. Serial changes in the SARS‐CoV‐2 antigen titer during the clinical course and treatment strategies for immunosuppressed patients are discussed. Abstract We report a case of prolonged SARS‐CoV‐2 infection during obinutuzumab and bendamustine treatment for follicular lymphoma. Four years previously, the patient had been diagnosed with follicular lymphoma (Stage IIIA, Grade 2). She received several chemotherapy regimens, including rituximab and radiation therapy. Although these therapies achieved complete response temporally, they did not continue and recurred at 8 months before. Obinutuzumab and bendamustine therapy was selected, and she received five courses of obinutuzumab and bendamustine. She also received a SARS‐CoV‐2 mRNA vaccine two times. Although she did not have any symptoms, a routine check‐up just before the 6th course of obinutuzumab and bendamustine revealed SARS‐CoV‐2 infection. Because she was immunosuppressed and was considered to be at high risk for the exacerbation of her disease, molnupiravir was immediately administered, and her SARS‐CoV‐2 antigen decreased. However, it was not completely cleared and flared‐up at 6 weeks, with symptoms of COVID‐19 appearing. Despite intensive treatment for SARS‐CoV‐2 infection, including remdesivir, baricitinib, tocilizumab and intravenous immunoglobulin, her SARS‐CoV‐2 antigen titer never became negative, and she finally died of respiratory failure caused by prolonged SARS‐CoV‐2 infection. Serial changes in the SARS‐CoV‐2 antigen titer during the clinical course and treatment strategies for immunosuppressed patients are discussed.